Choosing Methods in Mental Health Research: Mental Health Research from Theory to Practice, 1st edition - Slade, Mike, editor (Routledge, 2020)
Choosing Methods in Mental Health Research develops a new framework for mental health research. It is concerned with how to choose the most appropriate mental health research method, not only to address a specific question, but to maximize the potential impact on shaping mental health care.